Review of nitrogen nutrition in rice (Oryza sativa) growth and its relationship with fertilizer management practices / Norashikin Abd Rahman - Abd Rahman, Norashikin (Faculty of Plantation and Agrotechnology, 2017)
Understanding the factors that influence nitrogen concentration in rice plant is important to increase the rice productivity through the implementation of the efficient nitrogen fertilizer practices. Therefore, this review will focus on the optimum of nitrogen concentration in various plant parts such as leaf, root, stem, and grain as an indicator to determine deficiency levels of the crop. Nitrogen is essential for the plant growth, thus variations in concentrations at each stage of development will be examined and factors affecting the variation. Leaf nitrogen concentrations are declining as the plant age increase even though the plant uptake is rising. The leaves area index, photosynthesis rate, and assimilation process are the factor that contributes to the variances of nitrogen concentration in rice. By understanding the importance of nitrogen during the process of growth and development, it can provide guidance for suitable nitrogen management practices to attain maximum productivity. Though there are many management practices are in use but this paper will focus on the contribution of fertilizer type and rates on nitrogen uptake, effects of application timing and frequency of fertilizer application on grain yield.